Analisis Efektivitas Gaya Kepemimpinan Dan Profesionalisme Kerja Terhadap Kinerja Aparatur Yang Dimediasi Oleh Partisipasi Masyarakat (Studi Pada Aparatur Distrik Kaimana Kabupaten Kaimana) - Samirudin Samirudin (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This type of research is explanatory research, the approach used is a quantitative approach with the number of research samples as many as 59 apparatus. The purposes of this study are 1) To examine and analyze the leadership style has a significant effect on the performance of the apparatus of Kaimana District, Kaimana Regency. 2) Testing and analyzing leadership style has a significant effect on community participation in Kaimana District, Kaimana Regency. 3) Testing and analyzing professionalism has a significant effect on the performance of the Kaimana District apparatus, Kaimana Regency. 4) Testing and analyzing professionalism that has a significant effect on community participation in Kaimana District, Kaimana Regency. 5) Testing and analyzing community participation has a significant effect on the performance of the Kaimana District apparatus, Kaimana Regency. 6) Testing and analyzing leadership style has a significant effect on the performance of the Kaimana District apparatus, Kaimana Regency which is mediated by community participation. 7) Test and analyze professionalism which has a significant effect on the performance of the Kaimana District apparatus, Kaimana Regency which is mediated by community participation. The results showed that: 1) Leadership style had a significant positive effect on the performance of the Kaimana District apparatus, Kaimana Regency with an original sample value of 0.434. 2) Leadership style has a significant positive effect on community participation in Kaimana District, Kaimana Regency with an original sample value of 0.419. 3) Professionalism has a significant positive effect on the performance of the Kaimana District apparatus, Kaimana Regency with the original sample value of 0.356. 4) Professionalism has a significant positive effect on community participation in Kaimana District, Kaimana Regency with an original sample value of 0.297. 5) Community participation has a significant positive effect on the performance of the Kaimana District apparatus, Kaimana Regency with the original sample value of 0.306. 6) Leadership style has a insignificant positive effect on the performance of the Kaimana District apparatus, Kaimana Regency which is mediated by community participation with an original sample value of 0.128. 7) Professionalism has an insignificant positive effect on the performance of the Kaimana District apparatus, Kaimana Regency which is mediated by community participation with an original sample value of 0.091.